Integration of Islamic Educational Principles in Inclusive Curriculum for Children with Disabilities - Novanto, Riza Awal; Arifin, Syamsul; Ishomuddin, Ishomuddin (Lembaga Yasin AlSys, 2025)
This study explores the integration of Islamic educational values into an inclusive curriculum framework for children with disabilities, aiming to promote fair, comprehensive, and transformative education. As Indonesia increasingly recognizes the importance of inclusive education, there is a growing need for approaches that address not only academic but also spiritual and social dimensions. Employing a literature review methodology, the research analyzes scholarly articles, books, and official reports sourced from databases such as Google Scholar, JSTOR, and ProQuest. The analysis identifies three essential components for designing an inclusive curriculum grounded in Islamic values: (1) academic content tailored to the diverse needs of students with disabilities, (2) reinforcement of core Islamic principles such as patience, justice, empathy, and inclusiveness, and (3) pedagogical strategies that promote active participation and equity in the learning environment. While challenges such as limited resources and social stigma persist, opportunities exist in the form of teacher training, cross-sector collaboration, and supportive educational policies. The study underscores the potential of Islamic values to serve as a foundational framework for inclusive curriculum development in Indonesia, contributing to a more holistic and equitable educational system.